2023
DOI: 10.1002/tox.23762
|View full text |Cite
|
Sign up to set email alerts
|

Carvacrol reduces abnormal and dead sperm counts by attenuating sodium arsenite‐induced oxidative stress, inflammation, apoptosis, and autophagy in the testicular tissues of rats

Abstract: Background: The present study investigated the protective effects of carvacrol (CAR) against testicular toxicity induced by sodium arsenite (SA).Methods and Results: Rats were given SA and/or CAR for 14 days. Semen analyzes showed that CAR increased sperm motility and decreased the percentage of anarmol and dead sperm. It was determined that the oxidative stress induced by SA decreased with the increase of Nrf-2 and HO-1 expressions, SOD, CAT, GPx and GSH levels, and MDA levels decreased after CAR treatment. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…In the first, the addition of carvacrol increased levels of antioxidants and improved sperm quality parameters (Güvenç et al, 2018), whereas, in other study, the C was able to increase endogenous enzymatic and non‐enzymatic antioxidants in a group previously treated with cisplatin, a chemotherapy drug (Aksu et al, 2016). In addition, other studies also report the ability of this molecule to enhance the activity of antioxidant enzymes such as superoxide dismutase, catalase and glutathione peroxidase (Cicalău et al, 2021; Gur et al, 2023).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In the first, the addition of carvacrol increased levels of antioxidants and improved sperm quality parameters (Güvenç et al, 2018), whereas, in other study, the C was able to increase endogenous enzymatic and non‐enzymatic antioxidants in a group previously treated with cisplatin, a chemotherapy drug (Aksu et al, 2016). In addition, other studies also report the ability of this molecule to enhance the activity of antioxidant enzymes such as superoxide dismutase, catalase and glutathione peroxidase (Cicalău et al, 2021; Gur et al, 2023).…”
Section: Resultsmentioning
confidence: 97%
“…Finally, is remarkable that not much information is found approximately the use of C in sperm preservation, beyond therapeutic trials (Frydrychová et al, 2012;Gur et al, 2023;Güvenç et al, 2018). This study can be considered as a pioneer in the evaluation of carvacrol as an antioxidant for boar semen and opens the possibilities to evaluate other concentrations of this and its effect on other aspects of sperm integrity and metabolism.…”
Section: Re Sults and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Numerous studies have suggested that inflammation and oxidative stress play an important role in the pathophysiology of various diseases, such as lung, testis, liver, thyroid, and kidney toxicity and pulmonary fibrosis 34–44 . Moreover, emerging findings exhibited that Cat has obvious anti‐inflammatory, antioxidant, and antiapoptotic properties and its vital protective function in multiple organ damage 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it is essential to reveal the pathogenesis of SAKI, thereby paving the way for the develop- pulmonary fibrosis. [34][35][36][37][38][39][40][41][42][43][44] Moreover, emerging findings exhibited that Cat has obvious anti-inflammatory, antioxidant, and antiapoptotic properties and its vital protective function in multiple organ damage. 45,46 For instance, Xia et al manifested that Cat protected the spinal cord from spinal cord injury in mice through mediating microRNA-142-mediated HMGB1/TLR4/NF-κB signaling pathway.…”
Section: Cat Relieves Renal Damage Via Upregulating Sirt1 By Activati...mentioning
confidence: 99%